PENERAPAN AUGMENTED REALITY DENGAN KONTEN 3D MODELLING SEBAGAI SARANA BRANDING MULTIMEDIA KREATIF - Citra Devi Murdaningtyas; Laras Intansari; Artiarini Kusuma N (SENTIA 2016, 2016)
Creative Multimedia Department (MMK) is a new department in Electronic Engineering Polytechnic Institute of Surabaya. The existence MMK less well known in the community. Of these problems, it is necessary to MMK branding to the community. Branding is intended to provide an overview of MMK in a clear and informative with the use of today's technology in the form of Augmented Reality (AR) based 3D modeling. The 3D modeling will be presented in the form of the 3D shape of the tools that are at the laboratory practicum MMK. Based on testing AR marker on the application, it is concluded that the camera can detect a marker with a slope of less than 7°.